A Descriptive Study on Growth Profile of 100 Breastfeeding Children with Early Introduction of Infant Formulas in Abidjan, Côte d’Ivoire - Richard Azagoh-Kouadio; Kouadio Vincent Asse; Jean-Jacques Yao Atteby; Lassina Cisse; Jacob Slanziahuelie Enoh; Ehouman Mocket Adolphe; Stéphane Koffi-Djadan; Soumahoro Oulai (Current Topics in Medicine and Medical Research Vol. 13, 2021)
Objective: To describe the growth profile of breastfeeding babies following early introduction of infant formulas to improve the feeding pattern of the young infant. During the first 1000 days of life, uncontrolled feeding of the newborn increases the child’s risk of malnutrition which will later enhance the possibility of metabolic diseases such as obesity, diabetes and high blood pressure in adulthood. Methodology: This is a longitudinal descriptive study conducted in 2 medical clinics in Abidjan from 11-Jun-2013 to 15-Dec-2016 on 100 healthy newborn babies with the introduction of infant formulas before 6 months of life. The anthropometrics parameters were compared to those of WHO. Results: The exclusive breastfeeding rate was 5%. Ablactation occurred within 12 months in 95% of cases. All Infants have doubled and tripled their birth weight at 3 and 9 months respectively. The height and the head circumference at birth increased by 50% and 37% respectively at 12 months. Compared to WHO growth charts, the weight gain for the girls at 3 months was 12.4% higher and for the boys was 7.3% higher at 6 months. On the other hands, the statural gain at 12 months was 50% lower than the WHO standards while the head circumference was 37.8% and 45.5% higher than the WHO standards in boys and girls respectively. At 3 months, the prevalence of stunting was 26.1% for boys and 13.3% for girls. Lastly, at 12 months, the BMI showed 10% overweight and 19% obesity. Conclusion: Breastfeeding associated with an early introduction of infant formulas increases the risk of malnutrition of the young infant. We advise to avoid it and recommend an exclusive breastfeeding.